Exploring gender disparity in medicine: perceptions of female physicians in Lebanon - Kassouf, Sibelle (2024)
Background Global research on gender bias has highlighted key trends in discrimination and inequality across various fields, including medicine. In Lebanon, a nation celebrated for its diverse cultural landscape and increasing female representation in medical education, there has been a notable absence of studies exploring gender dynamics in the medical profession. Methods To address this gap, we conducted a cross-sectional study using an online survey to explore the Lebanese population’s perceptions towards female physicians and the quality of care they provide. Results The mean age of the study sample (n = 330) was 31.55 ± 10.07 years and included 114 females and 216 males. Most respondents had received care from a female physician. Notably, those who selected female physicians as their family doctors or had female doctors within their immediate family displayed a stronger tendency to engage in annual medical check-ups. While most respondents did not express any preference for the gender of their general practitioner or surgeon, there was a marked preference for female obstetricians/gynecologists, psychiatrists, pediatricians, and dermatologists. This preference was attributed to perceptions of female physicians being particularly compassionate, understanding, and proficient in communication. Conclusion This study represents a groundbreaking contribution to understanding gender perceptions in the Lebanese medical field. It highlights the growing trust and positive regard for female physicians, underscoring the significant role in shaping healthcare experiences and outcomes in Lebanon.